Cuban flora as a source of bioactive compounds - Oriela Pino Pérez; Fanny Jorgé Lazo; Ondina Leon Díaz; Bhupinder Khambay; Christopher Branford-White (International Journal of Cuban Studies, 2008)
Tropical flora constitutes a rich source of substances that can be applied directly, or as compounds, to the development of new pest control agents and Pharmaceuticals. Partly due to its great diversity, Cuban flora has not yet been closely studied as a potential source of chemical pesticides. Mass screening of a variety of plants is needed to determine the presence of bioactive compounds which could be used instead of commonly adopted agrochemicals and drugs. This study from the Centre for Plant Protection in Havana has focused on a selection of plants as potential sources of new natural products for botanical pesticides and medicines. For the first time in Cuba, this research has been carried out using a refined. Extracts from plants belonging to the Anacardiaceae, Asteraceae, Clusiaceae, Myrtaceae, Piperaceae, Anonaceae and Poaceae families were evaluated in terms of their effectiveness against bacteria, fungi, insects, mites and Artemia (brine shrimp). Plants from four of these families displayed activity and were then selected for further fractionation and purification. From a social and economic perspective, the identification of local candidates for developing phytosanitary products offers greater safety and efficiency for Cuban agriculture. This research could eventually assist other developing countries in developing national policies for agricultural management.